From ISIS terrorism to Pakistani counter-terrorism: evaluating violence - Seyed Ahmad Fatemi Nejad (رهیافتهای سیاسی و بین المللی)
After rising ISIS in Syria and Iraq, the possibility of its enlarging to other Islamic countries including Pakistan has been discussed on academic and security atmospheres. Meanwhile, there are two ambiguities: the first, how much does ISIS penetrate in Pakistan? Second, what is Pakistani reaction to ISIS penetration operationally? Given to numerous available claims in the both above ambiguities, it is possible to evaluate their validations regarding an indicator like prevalence of violence in Pakistan during the study period. So, the main aim here is to test the influence of ISIS in Pakistan in terms of violence. It seems that the prevalence of violence in Pakistan has not meaningful change under ISIS presence in the country. The hypothesis has been tested by explanatory method.